Effectiveness Of Educational Comics On Prevention Of Violence In Elementary School Children Penggilingan 09 Morning East Jakarta 2019 - Triana Indrayani; Nadya Namira; Rukmaini Rukmaini (Universitas STRADA Indonesia, 2020)
This study aims to determine the effect of the Effectiveness of Educational Comics on Prevention of Violence in Elementary School Children Penggilingan 09 Morning East Jakarta 2019. The research design used in this study was a pre-experimental design using the One Group Pre-Post-Test design, the sample in this study was 32 students taken using total sampling, the research instrument used a questionnaire, the data analysis used paired t test. The results showed that there were significant differences in the pretest and posttest after the educational comic intervention. There is a significant influence between the Effectiveness of Educational Comics on Prevention of Violence in State Elementary School Children before the intervention and after the intervention. It is expected that students will be more proactive in finding information about preventing violence in children so that they can apply the information obtained as well as possible